2017
DOI: 10.1007/978-3-319-52076-6_11
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Indoor Air Quality in UK Passivhaus Dwellings

Abstract: The adoption of the German Passivhaus Standard in the UK has grown rapidly in recent years. Stimulated by the shift towards energy efficient design and rising fuel costs, the concept is perceived as a potential means of meeting energy and carbon targets through an established, reliable methodology. However the performance of the Standard in terms of adequate indoor air quality and thermal comfort in a UK climate remains under-researched. This paper describes the use of the Passivhaus Standard in a UK context, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…They also observed that one of the biggest challenges for poor energy performance in Scottish Passivhaus homes was the lack of occupants' understanding of the MVHR system and the poor layout and ductwork. These findings are comparable to other parts of the UK, where the authors found that the lack of occupant knowledge in controlling the MVHR system was the main cause of IAQ problems [20]. They indicated that the CO 2 exceeded 1000 ppm in summer and winter in all homes, according to the 24 h monitored periods in summer and winter.…”
Section: Introductionsupporting
confidence: 79%
“…They also observed that one of the biggest challenges for poor energy performance in Scottish Passivhaus homes was the lack of occupants' understanding of the MVHR system and the poor layout and ductwork. These findings are comparable to other parts of the UK, where the authors found that the lack of occupant knowledge in controlling the MVHR system was the main cause of IAQ problems [20]. They indicated that the CO 2 exceeded 1000 ppm in summer and winter in all homes, according to the 24 h monitored periods in summer and winter.…”
Section: Introductionsupporting
confidence: 79%
“…In a slight irony, the success of these measures has been driven by one of the very few mandatory post-construction compliance requirements: airtightness testing. However, BPE testing of contemporary homes has indicated that ventilation strategies and the implementation of these may not be delivering adequate ventilation or good indoor air quality with consequent health impacts (Howieson, Sharpe, & Farren, 2014;McGill, Sharpe, Oyedele, Keeffe, & McAllister, 2017).…”
Section: Editorialmentioning
confidence: 99%
“…However, very few have compared the measured IAQ to the occupant's IAQ perception [29,45,46]. Other studies show conflicting results, suggesting that the IAQ in a Passivhaus may not be adequate [47][48][49]. Some of the Passivhaus principles, airtightness and ventilation, directly impact the IAQ in homes.…”
Section: Introductionmentioning
confidence: 99%